2015
DOI: 10.1111/puar.12435
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Employee Turnover in the Public Sector: Insights from Research on Teacher Mobility

Abstract: Employee turnover is a key area for public administration research, but one about which there is much still to be learned. Insights from an extensive body of research on employee turnover in a specifi c area of the public sector-public education-contributes to the understanding of employee mobility in public organizations more generally. Th e authors present a conceptual framework for understanding employee turnover that is grounded in economic theories of labor supply and demand, which have formed the foundat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
70
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(76 citation statements)
references
References 131 publications
3
70
0
3
Order By: Relevance
“…We also included the yearly salary of each agency head as a control variable. Previous research exploring public employees' turnover decisions found that salary is an important predictor of turnover rates (Geys, Heggedal, and Sørensen ; Grissom et al ). Although we cannot control for the labor market conditions because we cannot observe the outside options of each agency head, we included the salary level as a proxy for the opportunity costs of being dismissed.…”
Section: Methods and Datamentioning
confidence: 99%
See 2 more Smart Citations
“…We also included the yearly salary of each agency head as a control variable. Previous research exploring public employees' turnover decisions found that salary is an important predictor of turnover rates (Geys, Heggedal, and Sørensen ; Grissom et al ). Although we cannot control for the labor market conditions because we cannot observe the outside options of each agency head, we included the salary level as a proxy for the opportunity costs of being dismissed.…”
Section: Methods and Datamentioning
confidence: 99%
“…Since the continuous score is kept confidential and only the letter grades are publicly released, the discontinuities inherent in the assignment of grades offer an opportunity to investigate the impact of organizational performance on managerial turnover using a regression discontinuity design (RDD). This evidence is especially valuable given that “the dynamics of the relationship between turnover and performance remain uncertain” in public administration literature (Grissom et al , 247).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many of our school‐level controls, such as the percentage of low‐income students and support staff per student, are well established in the education literature as proxies for school‐level operating conditions (see, e.g., Ingersoll ), and so we expect that together they will do a reasonable job of fulfilling this purpose. At the same time, we look to the relevant theoretical and empirical literatures on employee turnover to guide our selection of school‐level controls (see, e.g., Eisenberger et al ; Fernet et al ; Grissom, Viano, and Selin ; Maslach, Schaufeli, and Leiter ). To the extent that our data allow, we have included all controls that are indicated by these literatures.…”
Section: Data Measurement and Methodsmentioning
confidence: 99%
“…The recruitment and training of public employees receives perennial attention (e.g., Ballou and Podgursky ; Brewer and Selden ; Meier and Hicklin ; Rainey and Steinbauer ; Shaw ), but the human capital resource base from which agencies draw their “raw materials” remains little examined. Accordingly, Grissom, Viano, and Selin () call for more careful consideration of supply and demand conditions in public administration labor markets.…”
Section: Task Complexity and Public Organizationsmentioning
confidence: 99%